PENGGUNAAN FRONTIER ORBITAL MOLEKUL SEBAGAI DESKRIPTOR PADA ANALISIS HUBUNGAN KUANTITATIF STRUKTUR AKTIVITAS (HKSA) TOKSIK SENYAWA KHLOROFENOL - Emdeniz, - (Universitas Andalas, 2012)
Quantitative structure-activity relationship (QSAR) methods have been applied to prediction of the toxicity of certain chemical compound. In this research a QSAR descriptor used frontier molecular orbital (LUMO energy (EL), HOMO energy (EH), and band gap (Î”E) and its derivatives were obtained from density functional theory (DFT) (chemical hardness (Î·) chemical potential (Î¼) or absolute electronegativity (Ï‡) and global electrophicility indeks (Ï‰)). Frontier molecular orbital (EL and EH) was calculated by ab initio quantum methods. This research found the correlation between the experimental ecotoxicological data of chlorophenols and toxicity prediction were calculated based on the best QSAR equation model of all equation model which have been studied. The best QSAR equation model using parameter LUMO energy (EL), and global electrophilicity index (Ï‰) as descriptor on QSAR toxic of chlorophenol compounds against Bacilus sp TL81 is - log IC50 = 11,022 - 1,767 EL - 5,687 Ï‰, and it has the coefficient of determination (R2) = 0,581 and standard deviation (SD) = 0,6111.